Depression, Anxiety, and Apathy in Mild Cognitive Impairment: Current Perspectives - Ma, Lina (Frontiers in Aging Neuroscience, 2020)
Objective: Mild cognitive impairment (MCI) is an important risk state for dementia, particularly Alzheimer’s disease (AD). Depression, anxiety, and apathy are commonly observed neuropsychiatric features in MCI, which have been linked to cognitive and functional decline in daily activities, as well as disease progression. Accordingly, the study’s objective is to review the prevalence, neuropsychological characteristics, and conversion rates to dementia between MCI patients with and without depression, anxiety, and apathy. Methods: A PubMed search and critical review were performed relating to studies of MCI, depression, anxiety, and apathy. Results: MCI patients have a high prevalence of depression/anxiety/apathy; furthermore, patients with MCI and concomitant depression/anxiety/apathy have more pronounced cognitive deficits and progress more often to dementia than MCI patients without depression/anxiety/apathy. Conclusions and implications: Depression, anxiety, and apathy are common in MCI and represent possible risk factors for cognitive decline and progression to dementia. Further studies are needed to better understand the role and neurobiology of depression, anxiety, and apathy in MCI.